Kepraktisan Bahan Ajar Statistika Pendidikan Fisika Bermuatan Model Cooperative Problem Solving - Afrizon, Renol; Dewi, Wahyuni Satria (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
The statistics of physics education are compulsory course with a lot of material descriptions so the lectures must be assisted by the use of teaching materials. The lectures of statistics of  physics education  that took place in the July-December 2017 semester illustrates that: 1) teaching materials are less attractive to students, 2) the assignments given are quite clear and sufficient in accordance with the level of thinking of students, 3) materials delivered by the lecturer is in accordance with the targets in the syllabus with some material is still abstract, 4) the lecture have been pursued in accordance with the syllabus but the methods used have not varied and 5) students learn material of statistic of physics education only from the lecturer explanation so that only a few students can answer statistical problems quickly and correctly. This indicates that it is need provided teaching materials with a cooperative problem solving model. The author has tried to design teaching materials of statistic of physics education  with cooperative problem solving models with very valid criteria according to the assessment of six experts with educational qualifications of statistics and physics education. However, this teaching material has not been tested at normal conditions in the lectures so that the level of practicality has not been revealed. The aim of this study was to determine the practicality level of educational statistical teaching materials containing cooperative problem solving models according to users, namely lecturers and students who listed in the course. Type of research is research and devel-opment with the ADDIE model. The ADDIE model stands for Analyze, Design, Develop, Implement and Evaluation. This research is part of the Implementation stage where development products are implemented in real terms so that the level of practicality can be measured with indicators of ease of use, attractiveness and efficiency. Data collection used student response questionnaires and lecturer response questionnaires with a Likert scale. Data analysis used descriptive statistic analysis techniques. The results showed that teaching materials of physics education statistics  had very practical criteria (lecturers opinion) and practical (students opinion). The conclusion of this study is the  teaching materials of statistic of physics education  with cooperative problem solving model  has been practically used in lectures